PROFITABILTY MANAGEMENT ANALYSIS IN BUSINESS STRATEGY AT PT UNILEVER INDONESIA TBK - Hardy Benry Simbolon; Daniel Hasibuan (Journal of Information System, Applied, Management, Accounting and Research, 2021)
In accordance with the concept of doing business, the main goal that the company wants to achieve when it is established is to obtain maximum profit or profit. Company profits and other information can be seen from the financial reports that the company regularly produces. However, this information will only be meaningful if the information in the form of numbers is then compared and analyzed for its value. PT Unilever Indonesia Tbk, which is a leading company in Indonesia which is engaged in the consumer goods industry, certainly has financial reports that are used by many parties. In addition, the condition and financial performance of the company, which has many household products, is certainly affected by the SARS-CoV-2 virus, which has been the cause of the pandemic in the world. In this study, the authors describe a simple analysis of the profitability ratio of PT Unilever Indonesia Tbk to measure the level of company profits and determine the company's ability to seek profit. This ratio is important for users of company financial reports to know, especially investors, so that they can find out the company's management performance during the time of the COVID-19 pandemic. Sesuai dengan konsep dalam berbisnis, tujuan utama yang ingin dicapai oleh perusahaan saat berdiri adalah memperoleh laba atau keuntungan yang maksimal. Laba perusahaan dan informasi lainnya dapat dilihat dari laporan keuangan yang secara rutin dibuat oleh perusahaan. Namun, informasi tersebut hanya akan menjadi berarti apabila informasi berupa angka-angka tersebut kemudian dibandingkan dan dianalisis nilainya. PT Unilever Indonesia Tbk yang merupakan perusahaan terkemuka di Indonesia yang bergerak dalam bidang industri consumer goods ini tentunya memiliki laporan keuangan yang digunakan oleh banyak pihak. Selain itu, kondisi dan kinerja keuangan perusahaan yang banyak memiliki produk rumah tangga ini juga tentu dipengaruhi oleh virus SARS-CoV-2 yang selama ini menjadi penyebab pandemi di dunia. Dalam penelitian ini, penulis menjabarkan analisis sederhana rasio profitabilitas PT Unilever Indonesia Tbk untuk mengukur tingkat keuntungan perusahaan dan mengetahui kemampuan perusahaan dalam mencari keuntungan. Rasio ini penting untuk diketahui oleh para pengguna laporan keuangan perusahaan terutama para investor untuk dapat mengetahui kinerja manajemen perusahaan dalam rentang waktu semasa pandemi COVID-19 ini.